MODERN MARRIAGE AND WEDDING RITUALS OF THE DARGINS-TSUDAHARS: TRADITIONS AND INNOVATIONS - Seferbekov, Ruslan Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2023)
Based on field ethnographic material collected in the Levashinsky district of Dagestan in 2018 and 2022, using historical-comparative, typological, systemic, retrospective methods and the method of participant observation, the paper discusses the traditional and modern wedding ceremonies and customs of the rural population of one of the sub-ethnic groups of the Dargins – the Tsudahars1. This group has undergone the cultural influence of the Avars of the Gunibsky and Gergebilsky districts and the Laks of the Laksky district, which is reflected in interethnic marriage, the spread of Avar anthroponymy, Avar khinkal, Avar and Lak music, songs and dances among the Tsudahar Dargins. The rituals of the life cycle of the Tsudahars, as well as other Dagestanis and North Caucasians, were influenced by the sociocultural processes of the late 20th – early 21st centuries, associated with “perestroika”, a change in the paradigm of the state and social structure of Russia, another Russian modernization and urbanization, which directly or indirectly modified them. The study shows that, despite the influence of globalization and transformation processes, almost all the main stages, characters, rituals and customs of the traditional Tsudahar wedding were mostly preserved only in rural areas. Relics of early forms of religions and ancient forms of marriage are still found in the modern Tsudahar wedding. The custom of mutual assistance has fully preserved, which makes it possible to mitigate the burden of material expenses for the wedding. Since the beginning of the 90s of the 20th century and to date, the need to reduce financial costs and the growing influence of the Muslim religion have led to the popularization of non-alcoholic weddings and the holding of wedding mawlids, replacing traditional wedding rituals with religious ones. In our time, real conditions have been created for the revival of some of the lost original elements of the Tsudahar wedding. The preservation of most of the traditional elements of the modern Tsudahar wedding inspires certain confidence in the preservation of their ethnic and cultural identity in the era of globalization.